INTELLECTUAL PROPERTY RIGHTS (IPR) ASPECT IN THE FRANCHISE BUSINESS FORMAT - Santoso, Budi (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2019)
In the franchise business, there are several aspects of IPR involved in it, such as trademark, copyright, patent either ordinary or simple, industrial design, and trade secrets. Each field of IPR has its own character and forms of legal protection that differ from one another, while the most basic aspects of IPR in the world of the franchise business, name brands and trade secrets. This study aims to analyze the correlation between aspects of Intellectual Property Rights and the franchise business format and which aspects of the IPR correlate with the format of the franchise business. The results show that the franchise agreement can be categorized as a principal agreement, involving the government, and the parties, while additional agreements, which are purely an agreement between the franchisor and the franchise, can be in the form of an agreement to maintain company secrets.